(untitled) (Research, Society and Development, 2020)
This study aims to analyze the Program of Performance Evaluation of Technical-Administrative in Education of the Public University in southern Brazil, from its origin to the present time. The methodology is of qualitative nature, through content analysis and interview application. The results reveal an intervention proposal, combined with theory and document analysis, based on the following actions: to establish concepts for factors that integrate the evaluation, to expand the number of analyzed factors, to modify the classification scale and its conceptualization, to include issues involving management activities, work team evaluation and user evaluation, to include working conditions evaluation stage, to add training demands, to invest in training for evaluators and evaluated, to sensitize evaluators and evaluated about the importance of the evaluation process and the feedback stage, to estimate indicators and targets for the evaluation process and to adjust the system so that it can generate performance evaluation reports.